Condições de saúde de mulheres adultas de acordo com raça em dois municípios do Rio Grande do Sul - Bairros, Fernanda Souza de (Universidade do Vale do Rio do Sinos, 2006)
Objective: To investigate the access of both Black and White women to cancer early detection exams, breast and pap-smear, in two cities in Southern Brazil.Methods: A population based cross-sectional study that combines two representative samples of women aged from 20 to 60 years, from São Leopoldo and Pelotas, south Brazil cities. The analyses were adjusted according to income, education, economic class and age in order to verify the association of race/color with the access to pap-smear and breast exam. Results: Out of 2030 women interviewed, 327 (16.1%) were Black and 1703 (83.9%) were White. In comparison with White women, there were higher percentages of Black women in the lower strata of income, economic class and education. The probability of not accomplishing pap-smear and breast exam was significantly higher among Black women. Racial inequalities in access to cancer early detection exams persisted after controlling for age and other socioeconomic variables. In the previous year, Black women, regardl
Keywords: acesso; citopatológico; exame de mama; desigualdade racial; saúde da mulher; serviços de saúde; breast exam; pap-smear; racial inequality; access; health services; woman’s health; Ciências da Saúde